1965
DOI: 10.1037/h0022158
|View full text |Cite
|
Sign up to set email alerts
|

Birth order and scholastic aptitude.

Abstract: It was hypothesized that entering Ist-born college students should earn higher mean scores on the Mathematics Aptitude test (MAT) and the Verbal Aptitude test (VAT) of the College Entrance Examination Board than would later borns. Data on 1,878 students entering in 1960 and 1961 were available, though only those (80% of total) coming from families of 2, 3, and 4 children entered in the study. The hypothesis held for female students on the VAT (t of 3.4S), but the corresponding t of 1.S9 favoring the higher mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1
2

Year Published

1972
1972
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 7 publications
0
21
1
2
Order By: Relevance
“…There is some evidence to support the idea that the lack of an opportunity to teach may have a detrimental effect on intellectual development (Allen, 1976;Allen & Feldman, 1974;Devin-Sheehan, Feldman & Allen, 1976). Relatively low intelligence scores for last borns and only children have been observed in a number of studies (Altus, 1965;Belmont & Marolla, 1973;Breland, 1974).…”
Section: Features Of the Confluence Modelmentioning
confidence: 91%
“…There is some evidence to support the idea that the lack of an opportunity to teach may have a detrimental effect on intellectual development (Allen, 1976;Allen & Feldman, 1974;Devin-Sheehan, Feldman & Allen, 1976). Relatively low intelligence scores for last borns and only children have been observed in a number of studies (Altus, 1965;Belmont & Marolla, 1973;Breland, 1974).…”
Section: Features Of the Confluence Modelmentioning
confidence: 91%
“…The literature regarding the effects of ordinal position on intellectual activities is inconsistent, with some studies emphasizing the superiority of the first born (Altus, 1962;Koch, 1954;Terman, 1947) and some the superiority of the second born (Hsiao, 1931;McFadden, 1929;Thurstone & Jenkins, 1929). Except for Koch's study with six-year-olds, there has been no control for age, socia-economic status, or family size.…”
Section: Probledlmentioning
confidence: 99%
“…Only those reviews by Altus and by Schachter argued strongly for the existence of a relationship (that earlyborn, and especially firstborn, have higher achievement). Altus (1965) suggested that the observed relationship was due to a verbal factor. Most of the other reviewers indicate that little evidence exists for a relation ship between birth order and intelligence or other achievement indicators.…”
Section: Educational Testing Servicementioning
confidence: 99%